Safety skills training for surgeons: A half-day intervention improves knowledge, attitudes and awareness of patient safety. - Arora, S; Sevdalis, N; Ahmed, M; Wong, H; Moorthy, K; Vincent, C (2012)
BACKGROUND: Education and training of health care professionals is necessary to achieve sustainable improvements in patient safety. Despite its inherently risky nature, little training specifically in safety has been conducted in the surgical disciplines. In this study we explored the effects of a safety skills training program on surgical residents' knowledge, attitudes, and awareness of patient safety. METHODS: A half-day training program incorporating safety awareness, analysis, and improvement skills was delivered to surgical residents from 19 hospitals in London, United Kingdom. Participants were assessed in terms of safety knowledge (MCQs) and attitudes to safety (validated questionnaire; scale 1 to 5) before and after training. To determine long-term effects, 6 months after training participants identified and reported on observed safety events in their own workplace by using an observational form for data collection. RESULTS: A total of 27 surgeons participated in the training program. Knowledge of safety significantly improved after the course (mean pre = 45.26% vs mean post = 70.59%, P < .01) as did attitudes to error analysis and improving safety (mean pre 3.50 vs mean post 3.97, P < .001) and ability to influence safety (mean pre 3.22 vs mean post 3.49, P < .01). After the course, participants reported richer, detailed sets of observations demonstrating enhanced understanding, recognition, and analysis of patient safety issues in their workplace. CONCLUSION: Safety skills training with positive educational outcomes can be delivered in a half day. Such a course may allow patient safety to be integrated into any curriculum, thereby training the next generation of the healthcare workforce to maintain the safety momentum.